Československo – Polsko – východní Evropa. Počátek a konec osmdesátých let 20. století v pramenech Jihočeského krajského výboru Komunistické strany Československa v Českých Budějovicích - Petráš, Jiří (Komunizm: System - Ludzie - Dokumentacja, 2023)
The very end of the eighties meant a significant turning point in the international situation. While at the beginning of this decade the Soviet bloc of European countries appears as a solid monolith, which crumbled in only one place - Poland, on the opposite side of the same decade, the situation was vastly different. So it happened that at this time the citizens of Czechoslovakia could travel to the Hungarian People's Republic to visit concerts of western bands and singers and also to Poland for even more emotional experience – to see and hear on their own eyes such icons as Karel Kryl and Jaroslav Hutka. The crisis of Polish and Czechoslovak society as well as PSDS and the Communist Party framed the last decades of the Soviet bloc in Central and Southeastern Europe. Of course, it varied in many ways considerably, but it can be also said that also many features they have in common. The were based on the difference in the history of both nations - states, at least since the end of the World War II. In Czechoslovakia, unlike Poland took place in the fifties consistent villages collectivization and nationalization of industry, trade completely disappeared and society was mostly unreligious. The account must also take a different breed of both nations - on the one hand, Josef Švejk, on the other pan Wolodiowski. In both cases, however, the ruling party has lost the confidence of the masses, the economic system laid out and well - global changes played a decisive role.